Pengaruh Pemberian Seduhan Kunyit Asam Terhadap Penurunan Tingkat Dismenorea pada Siswi SMPN 19 Bandar Lampung Provinsi Lampung - Clara Sartika; Kamidah Kamidah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Menstruation is the process of shedding of the uterine wall (the inner layer of the endometrium) which is accompanied by bleeding that occurs repeatedly every month, except during pregnancy. Dysmenorrhea consists of primary and secondary dysmenorrhea. This study aims to determine the impact of giving sour turmeric infusion on changes in the level of dysmenorrhoea. Giving tamarind turmeric infusion on changes in desmenorrhea in female students at SMPN 19 Bandar Lampung. Research Objective: To determine the impact of giving sour turmeric infusion on changes in the level of dysmenorrhoea in female students at SMPN 19 Bandar Lampung Research Method: The type of research used is quantitative with a cross sectional approach. Pre-experimental research design with a one group pretest-posttest design without a control group. The sampling technique uses the Accidental Sampling technique. The data analysis technique used is the Wilcoxon test. Research result : Giving tamarind turmeric is a feasible intervention given to reduce dysmenorrhea pain experienced by young women. Suggestion for health workers to provide knowledge about treatment non-pharmacological dysmenorrhoea by administering tamarind turmeric drink. Conclusion : Giving tamarind turmeric is a suitable intervention to reduce dysmenorrhea pain experienced by young women. Suggestions for health workers to provide knowledge about non-pharmacological treatment of dysmenorrhoea by giving tamarind turmeric drinks